USE OF NEGATIVE PRESSURE IN WOUND THERAPY - Todorovic, Slobodan; Tošković, Borislav; Gačić, Jasna; Čolaković, Nataša; Kostić, Jelena; Guslarević, Stefan; Nadj, Igor; Mrda, Jovana; Todorović, Tatjana; Jazvo, Hana; Crnokrak, Bogdan (Srpski medicinski časopis Lekarske komore, 2023)
The use of negative pressure in wound therapy is an innovative therapeutic method that accelerates the wound healing process. This technique is applied to various types of acute and chronic wounds and can shorten their healing time and improve the quality of the scars. Negative pressure therapy acts on the wound by improving blood circulation, reducing swelling, promoting the growth of granulation tissue, reducing the risk of infection, and improving the quality of scar formation. At the molecular level, negative pressure increases the expression of cytokines and growth factors that promote angiogenesis, extracellular matrix remodeling, and tissue regeneration. Negative pressure therapy, as one of the techniques for temporary abdominal closing, is used in situations where the abdominal cavity must remain open for some time, in complex injuries, infections, and where there is a risk of compartment syndrome. In recent years, endoscopic vacuum therapy, a minimally invasive modality of treatment in colorectal surgery and surgery of the upper gastrointestinal tract, has emerged. The possibilities of this therapy have not been completely exhausted. In addition to its multiple applications, it has been shown that negative pressure therapy reduces treatment costs, shortens the duration of hospital stay, and enables faster patient recovery.